ANALISIS PERMASALAHAN GERAK LOKOMOTOR SISWA KELAS I SD DAN UPAYA PENINGKATANNYA MELALUI PEMBELAJARAN BERBASIS PERMAINAN : . - Rosmaniar; Bintan, Zirmayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze and describe the problems of locomotor movement ability in first-grade elementary school students, and to improve this ability through the application of game-based learning in physical education. This Classroom Action Research (CAR) was conducted in two cycles with 28 first-grade students of SDN 235 Goarie as subjects. Data collection techniques included observation, motor skill tests, interviews, and documentation, analyzed using descriptive quantitative and qualitative methods. The results showed that in the pre-cycle stage, the average locomotor ability reached only 40.1%. After Cycle I using simple games, the average increased to 60.9%, and in Cycle II, which combined varied games with music and teaching aids, the average rose significantly to 76.8%, surpassing the 75% classical mastery target. Jumping and galloping were found to be the most problematic movements, while walking and running were more easily mastered. It is concluded that the gradual and systematic application of game-based learning can significantly improve the locomotor ability of first-grade students. Teachers are recommended to integrate various motor games into physical education from an early stage.